Neuromuscular recruitment strategies of the vastus lateralis according to sex. (2nd March 2022) - Guo, Yuxiao; Jones, Eleanor J.; Inns, Thomas B.; Ely, Isabel A.; Stashuk, Daniel W.; Wilkinson, Daniel J.; Smith, Kenneth; Piasecki, Jessica; Phillips, Bethan E.; Atherton, Philip J.; Piasecki, Mathew
Abstract: Aim: Despite males typically exhibiting greater muscle strength and fatigability than females, it remains unclear if there are sex‐based differences in neuromuscular recruitment strategies e.g. recruitment and modulation of motor unit firing rate (MU FR) at normalized forces and during progressive increases in force. Methods: The study includes 29 healthy male and 31 healthy female participants (18‐35 years). Intramuscular electromyography (iEMG) was used to record individual motor unit potentials (MUPs) and near‐fibre MUPs from the vastus lateralis (VL) during 10% and 25% maximum isometric voluntary contractions (MVC), and spike‐triggered averaging was used to obtain motor unit number estimates (MUNE) of the VL. Results: Males exhibited greater muscle strength ( P < .001) and size ( P < .001) than females, with no difference in force steadiness at 10% or 25% MVC. Females had 8.4% and 6.5% higher FR at 10% and 25% MVC, respectively (both P < .03), while the MUP area was 33% smaller in females at 10% MVC ( P < .02) and 26% smaller at 25% MVC ( P = .062). However, both sexes showed similar increases in MU size and FR when moving from low‐ to mid‐level contractions. There were no sex differences in any near‐fibre MUP parameters or in MUNE. Conclusion: In the vastus lateralis, females produce muscle force via different neuromuscular recruitment strategies to males which is characterized by smaller MUs discharging at higher rates. However, similar strategies are employed to increase force production from low‐ to mid‐level contractions. These findings of similar proportional increases between sexes support the use of mixed sex cohorts in studies of this nature.